Allele frequency estimation of BLAD (Bovine Leukocyte Adhesion Deficiency) in dairy cattle in Enrekang regency South Sulawesi Indonesia. (November 2018) - Dagong, M I A; Rahim, L; Aprilita Bugiwati, R R S R; Nurmulyaningsih,
Abstract: Bovine leukocyte adhesion deficiency (BLAD) is a genetic disorder in dairy cows that are generally lethal or premature in cattle that can have an impact on productivity and result in losses for farmers. The purpose of this study is to identify the distribution of the BLAD recessive allele in dairy cows raised in Enrekang dairy cattle development centers. Identification of recessive BLAD allele using the PCR-RFLP method. A total of 80 DNA samples in a collection of blood samples from FH dairy cows from Enrekang regency (50 heads from Cendana and 30 heads from Anggeraja district) were extracted and amplified by PCR, then the PCR product was cut with the Taq1 restriction enzymes. The identification of the BLAD carrier alleles is calculated according to the frequency of genotypes and alleles. The results obtained from this study is (+/-) heterozygous cows (BLAD carrier) found 1 head (with a frequency of the allele (-) (BLAD recessive) of 0.01) in the Cendana district of 50 samples, while the Bovine population in the district Anggeraja did not found any BLAD recessive allele. The results of this study concluded that there is a normal heterozygous dairy cows (BLAD carrier) in the dairy cows population in the Enrekang regency, although the proportion / frequency of alleles is very low (0.625%). This research can be used as a reference in selecting dairy cattle, especially those related to the spread of lethal alleles in dairy cattle development areas in South Sulawesi.